The fifth doctrine - Robards, Karen (Mira, 2019)
Offered her freedom in exchange for a dangerous undercover assignment, master manipulator Bianca St. Ives poses as a female hacker who stole top secret intel from NORAD in order to feed strategic misinformation to North Korea's tyrannical regime.